Методические основы применения активных методов обучения студентов - Смоловик, Раиса Федоровна; Линник, Елена Ивановна; Яровая, В. И.; Лебеденко, И. В. (Харьковский государственный политехнический университет, 1998)
The methodical instructions for teaching students of institutes and universities have been stated by the means of active methods, such as: playing projects, business games and so on. It was underlined that such methods of teaching ensured the efficacy in the process of getting knowledge.
Keywords: высшее техническое образование; методы обучения; эффективность обучения; игра как метод обучения